Kontribusi Mahasiswa dalam Merealisasikan Kreativitas Diri Melalui Model Pembelajaran Special Event di Politeknik Pariwisata Prima Internasional - Fitriatunnisa Shabrina; Dian Fitriyana; Joseph Aldo Irawan; Aji Kusumah Ramdhani; Mohammad Saeful Rohman; Hardiyanti Ayu Lestari; Laura Valentina Avelyra; Asinta Asinta (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
Creativity is an activity that positively impacts human growth and development. One form of human growth and development is the output of creativity through an activity and a product. EPHICS emerged as a form of creativity from international prime tourism polytechnic students and involved students. Qualitative descriptive methods followed by observation and visualization of layouts assisted by the interview process and documentation to collect data related to research. As a result of this activity program, students make a field learning model that can continue to hone creativity and is expected to develop EPHICS even better. SWOT analysis and analysis of the concept of event implementation become the basis for the activity evaluation process. The evaluation results obtained after each activity is completed are used as material for improvement in the implementation of future EPHICS activities to make it even better.